2007
DOI: 10.1063/1.2751599
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic range of nanoresonators with random rough surfaces in the presence of thermomechanical and momentum exchange noise

Abstract: Citation for published version (APA): Palasantzas, G. (2007). Dynamic range of nanoresonators with random rough surfaces in the presence of thermomechanical and momentum exchange noise. Applied Physics Letters, 91(2), [021901].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…For consistency an analytical estimation of S total was performed. For this we used the rough area calculation 18,25,26 S rough /S smooth…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For consistency an analytical estimation of S total was performed. For this we used the rough area calculation 18,25,26 S rough /S smooth…”
Section: Resultsmentioning
confidence: 99%
“…16 Recently it was shown theoretically that random surface roughness affects the quality factor, limit to mass sensitivity, Allan variance, and dynamic range of resonators. 17,18 However, so far a systematic experimental study of the influence of surface roughness on the quality factor of resonators is still missing. This will be the topic of the present paper, where we explore the dependence of the Q factor on the surface morphology of commercial microcantilevers (Table I) at various gas pressures covering the whole range from the free molecular up to the continuous regime (ambient regime ∼1 atm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, random surface roughness was shown to affect the quality factor, the limit to mass sensitivity of nanoresonators, and their dynamic range. [10][11][12] In addition, another important quantity that is very often used to compare frequency standards and thus quantify frequency fluctuations is the dimensionless Allan variance ͑ A ͒. 6,13,14 The latter is defined in the time domain as the variance over time in the measured frequency of a source, where each measurement is averaged over a time interval A ͑with zero-dead time between measurement intervals͒.…”
Section: Allan Variance Of Frequency Fluctuations Due To Momentum Excmentioning
confidence: 99%
“…13 Recently, within the molecular regime ͑molecule mean free path larger than the lateral nanoresonator dimensions͒, it was shown that random surface roughness can decrease the quality factor and dynamic range, and increase the limit to mass sensitivity. [14][15][16] Furthermore, under operation in dense fluid, a high resonance-frequency nanomechanical resonator generates a rapidly oscillating flow in the surrounding fluid environment. 10,11 Over a broad frequency ͑͒ and pressure ͑P͒ range explored, it was observed a sign of a transition from Newtonian to non-Newtonian flow at Ϸ 1 with a fluid relaxation time.…”
Section: Surface Roughness Influence On the Quality Factor Of High Frmentioning
confidence: 99%